Behind 11 million likes: Sustainable fashion on Instagram ‐ A critical analysis of actors and discourses on fashion, sustainability and social change. Issue 1 (1st April 2022) - Vladimirova, Katia
Social media has become an indispensable part of the daily lives of billions of people globally and, among its many functions, provides online space for conversations about socially important topics. Sustainability dimensions of the fashion system is a growing area of public interest, both in terms of production and consumption practices. This study explores online conversations about sustainable fashion on Instagram and maps the ongoing discourse in terms of actors, themes and views of social change that is required to achieve more sustainability in the fashion system. Instagram is a photo-sharing app owned by Facebook and a social media network of choice of the Millennial and Gen Z women, who are also main consumers of fast fashion, which makes it the perfect source of data for discourse analysis. Using the CrowdTangle tool, the 500 most influential Instagram posts that contained references to sustainable fashion from March 2020 to February 2021 were analysed. The analysis revealed that Instagram discourse on sustainable fashion is dominated by product-promoting messages from brands that communicate directly using their accounts or via collaborations with influencers. While the discourse is polycentric and there are many actors behind the most influential posts, the most numerous communications are from two brands: H&M (@hm) and Reliance Polyester (@r.elan.official). In terms of discussions about social change, these conversations were present almost exclusively in non-sponsored posts of influencers, media, industry associations and non-profit organizations. Social change is discussed in relation to the production side of the fashion system, including nuanced reflections on the role of systemic racism and poverty in fashion supply chains, moving towards local production and using new business models to scale down. However, the main emphasis in references to social change is on consumers' actions and choices rather than on systemic change: buying less and refusing fast fashion, switching to second hand and using garments for longer.